Emotional Effects on University Choice Behavior: The Influence of Experienced Narrators and Their Characteristics - Callejas-Albiñana, Ana I.; Callejas-Albiñana, Fernando E.; Martínez-Rodríguez, Isabel (Frontiers in Psychology, 2016)
This study analyzes the influence that experienced users of university resources might have as narrative sources of information for other students in the process of choosing their schools. Informative videos about the benefits of studying at the university provide a reference model. In these videos, a group of young people present their views and explain their reasons for choosing the university in which they are pursuing their degrees; the various narrators detail all the resources available. This study investigates whether the individual identifiers of these narrators (e.g., gender, age, physical appearance, nonverbal gestures such as smiling, posture) influence perceptions of the credibility of the information they provide. Among a sample of 150 students in their last year of pre-university training, the results demonstrate that the students’ ability to identify with the narrators provides information and arouses emotions that inform their perceptions of reliability and therefore their consumption choices. None of these predictors appear to serve as determinants that can be generalized, but if emotional attitudes in response to narratives about the topic (i.e., the university) are positive, then they prompt a change in attitude toward that reference topic too.